EVALUATION FACTORS OF BOAT ACCIDENTS IN THE MUSI RIVER WATERS, INDONESIA - Surnata Surnata; Febriansyah Febriansyah; Ferdinand Pusriansyah; Monica Amanda; Destria Rahmita (LPPM STIE Muhammadiah Bandung, 2022)
Musi River is a river placed in South Sumatra, Indonesia. The Musi River is also the biggest river with a median width of 504 meters (the widest is 1350 meters round Kemaro Island, and the shortest 250 meters is positioned around the Musi II River Bridge).The only means of transportation that can reach the area is by boat via the Musi River. People use the Musi River as a transportation route to travel from one place to another around Palembang City or to areas far from Palembang City and use ships to travel in order to shop for daily needs, work and others. However, in the operation of the ship on its way there are still accidents, which often occur are accidents caused by human error, besides that there are often obstacles with natural conditions. For example, waves and on every bank of the Musi river, there are lots of tree plants that interfere with the smooth flow of traffic. Recently, in the Musi River there was an accident other than in Akibarka, the natural condition of the accident was caused by human negligence Two speedboats with the brand Rahendi Putra and Five Brothers collided while in the waters of the Musi River, Palembang, South Sumatra (South Sumatra), Wednesday (30/5/2018). Accidents in the Last Two Years Tuesday on the Awet Muda speedboat revealed new facts. In the last two years, the fast boat company has had two accidents that claimed lives.